2015
DOI: 10.4236/jacen.2015.42004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composts Combined with Chemical N Fertilizer on Nitrogen Uptake by Italian Ryegrass and N Transformation in Soil

Abstract: Combining compost with sufficient chemical N fertilizer (CF) in agricultural lands is a popular practice to reduce the amount of inorganic nitrogen and accumulation of non-nutrient constituents in soils. A pot culture experiment was conducted to study the effects of 130 mg N of either solids waste compost (Scomp) or biosolids waste compost (Bcomp) complemented with 130 mg (CF, 1N) and 260 mg•N•pot −1 (CF, 2N) as 15 N labeled (NH4)2SO4 (13.172 atom %) on growth and N uptake by Italian ryegrass. A separate soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Chemical analysis: Total N and C content were determined using a CN-Analyzer. 15N isotope ratios were measured in plants and soil samples (from stable isotope culture containers) using the CN-Analyzer coupled with isotope Quadrupole mass spectrometry [14].…”
Section: Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical analysis: Total N and C content were determined using a CN-Analyzer. 15N isotope ratios were measured in plants and soil samples (from stable isotope culture containers) using the CN-Analyzer coupled with isotope Quadrupole mass spectrometry [14].…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Despite higher leaching potential, urea-N applied as an additional fertilizer can provide an important role for an effect rate of MSW treatment. Combining the application of organic compost and inorganic fertilizer to crops has been shown to be more effective in increasing the yield than an application of either fertilizer type alone [14]. Further, Han et al [17] showed that a blend of chemical fertilizers and compost could increase the mineralization rate of compost-N.…”
Section: B Dynamics Of Compost-n Amended Soilmentioning
confidence: 99%
“…Predicting nitrogen (N) mineralization from compost plays an important role from both agricultural and environmental point of view. The available N derived from sewage sludge compost has been found to depend on gross N mineralization and gross N immobilization turnover (MIT) [1]. One of the most common problems associated with utilization of composted sewage sludge in advanced agricultural Manuscript received April 24, 2017; revised October 9, 2017. technologies is the risk of nitrate (NO 3 -N) leaching into the groundwater through application of fast-release Nfertilizers [2], [3].…”
Section: Introductionmentioning
confidence: 99%